Mechanical Heart Valve Replacement in a Low-Middle Income Region in the Modern Era: Midterm Results from a Sub-Saharan Center - Mve Mvondo, Charles; Pugliese, Marta; Ambassa, Jean Claude; Giamberti, Alessandro; Bovio, Emanuele; Dailor, Ellen (The Thoracic and Cardiovascular Surgeon, 2020)
Background The management of patients with mechanical heart valves remains a major concern in populations with limited resources and medical facilities. This study reports the clinical outcomes of patients who underwent mechanical valve implantation in a sub-Saharan center over an 8-year period.Methods A total of 291 mechanical valves were implanted in 233 patients in our institution between February 2008 and June 2016. A total of 117 patients underwent mitral valve replacement (MVR, 50.2%), 57 had aortic valve replacement (AVR, 24.4%), and 59 underwent both AVR and MVR (double valve replacement [DVR], 25.7%). The mean age at surgery was 27.6 ± 13.4 years (range, 7–62 years). Rheumatic etiology was found in 80.6% of the patients. Hospital mortality, late deaths, and valve-related events were reviewed at follow-up (839 patient-years, range: 1–9.4 years, complete in 93%).Results The 30-day mortality was 4.7% (11/233). The overall survival at 1 and 6 years for the whole cohort was 88.8 ± 2.1% and 78.7 ± 3.3%, respectively. The 6-year survival for AVR, MVR, and DVR was 89.3 ± 4.8%, 73.2 ± 5.4%, and 79.3 ± 5.8%, respectively (p = 0.15). The freedom from neurologic events and anticoagulation-related bleeding at 6 years was 93.1 ± 2.1% and 78.9 ± 3.7%, respectively. No patient had reoperation at follow-up. No case of prosthetic valve thrombosis was identified. Eight full-term pregnancies were reported.Conclusion This preliminary experience reports acceptable midterm results after mechanical heart valve implantation in our region. Both accurate surgical evaluation and strategies, either financial or social, facilitating patient's education and medical assistance are crucial to ensure good results. Long-term follow-up and further studies comparing current nonthrombogenic options are warranted to draw reliable conclusions.
Keywords: mechanical valve; developing countries; rheumatic disease